Synthesis, biological evaluation and structure-activity relationships of new quinoxaline derivatives as anti-Plasmodium falciparum agents (2014)
ABSTARCT: We report the synthesis and antimalarial activities of eighteen quinoxaline and quinoxaline 1,4-di-N-oxide derivatives, eight of which are completely novel. Compounds 1a and 2a were the most active against Plasmodium falciparum strains. Structure-activity relationships demonstrated the importance of an enone moiety linked to the quinoxaline ring. Keywords: Plasmodium falciparum; antimalarial agents; quinoxaline; quinoxaline 1,4-di-N-oxide; chalcone